Challenges in the management of giant cardiac rhabdomyoma in a toddler: unresponsive to everolimus therapy - Tamer, Reyhan; Otçu Temur, Hafize; Yurtsever, İsmail; Yozgat, Can Yılmaz; Talebazadeh, Faraz; Kuş, Hazar Doğuş; Erol, Ahmet Berk; Yozgat, Yılmaz (My University, 2024)
...
Herausforderungen bei der behandlung eines riesigen kardialen rhabdomyoms bei einem kleinkind: keine reaktion auf everolimus-therapie
Keywords: Article; Cardiac Rhabdomyoma; Diagnosis; Human; Therapy; Toddler